PENGARUH BRAND IMAGE DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN PADA COFFEE SHOP FORTHIS HOUSE SAMARINDA - Wati, Indah Permata Mega; Ellyawati, Noor; Abu, Ilham (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
This study aims to determine the effect of brand image and word of mouth onconsumer purchasing decisions at the coffee shop Forthis House Samarinda. Thisresearch method is descriptive-quantitative, using data collection techniques suchas observation, documentation, questionnaires, and interviews. The population inthis study were consumers at the Forthis House Samarinda coffee shop. Thesampling technique in this study used non-random sampling, namely purposivesampling, with a sample of 97 respondents. The analysis technique used is multiplelinear regression analysis with the SPSS version 29 application. The results of thisstudy indicate that from the results of the calculation of the partial test or t test onbrand image, the result of t count 6.252 > t table 1.985 and word of mouth obtainedt count 3.440 > t table 1.985 with a significance of 0.01 <0.05 which means thatBrand Image and Word of Mouth have a partial and significant effect on consumerpurchasing decisions at the coffee shop Forthis House Samarinda. The results ofthe simultaneous test or F test in this study obtained F count of 76.996 > F table3.09 with a significance of 0.01 <0.05, which means that brand image and word ofmouth have a simultaneous and significant effect on purchasing decisions at theForthis coffee shop, House Samarinda.